2018
DOI: 10.1186/s12917-018-1596-8
|View full text |Cite
|
Sign up to set email alerts
|

Rift Valley fever seroprevalence and abortion frequency among livestock of Kisoro district, South Western Uganda (2016): a prerequisite for zoonotic infection

Abstract: BackgroundRift Valley fever (RVF) is classified as viral hemorrhagic fever and is endemic in East and West Africa. RVF is caused by an arthropod borne virus (RVFV); the disease is zoonotic and affects human, animal health as well as international trade. In livestock it causes abortions, while human infection occurs through close contact with infected animals or animal products.MethodsA quantitative observational study using stratified sampling was conducted in the western region of Uganda. Blood samples and ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 36 publications
(37 reference statements)
4
20
0
Order By: Relevance
“…Ntwetwe virus was most likely referred to as an arbovirus vectored by Anopheles mosquitoes. There has not been any other case of Ntwetwe virus from this region; hence, the case of this girl child was a rare and unique Pathogens 2020, 9,301 16 of 83 event. The study suggested that mosquitoes or an animal reservoir might be the probable source of transmission of this virus disease [74].…”
Section: Ugandamentioning
confidence: 83%
See 1 more Smart Citation
“…Ntwetwe virus was most likely referred to as an arbovirus vectored by Anopheles mosquitoes. There has not been any other case of Ntwetwe virus from this region; hence, the case of this girl child was a rare and unique Pathogens 2020, 9,301 16 of 83 event. The study suggested that mosquitoes or an animal reservoir might be the probable source of transmission of this virus disease [74].…”
Section: Ugandamentioning
confidence: 83%
“…The results revealed that 70 cattle were seropositive for RVFV along with 22 sheep and 12 goats. The outcome of this investigation suspected the zoonotic spread of the disease in Kisoro district [9].…”
Section: Ugandamentioning
confidence: 84%
“…These results indicate that livestock could be involved in the amplification of RVFV in Gezira. The most infected species was goats, while in other RVF outbreaks, such as in Uganda, cattle played a more important role [10]. Unfortunately, the result of the survey was not distributed at the locality level of Gezira state in order to incorporate it in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…RVF causes serious health and economic problems. In animals, RVF affects different species and causes death particularly in lambs [9], and in pregnant livestock, RVF can cause abortion [9, 10]. This often leads to severe socioeconomic impacts in affected countries [11–13].…”
Section: Introductionmentioning
confidence: 99%
“…The age of the animal plays an important role in an animal’s susceptibility to a severe form of RVF [ 29 ]. For example, the mortality rate in lamb and adult sheep was 90% and 20–60%, respectively, while the abortion in pregnant ewes can reach 100% [ 30 ]. The disease was less severe in cattle and camels with a 10–30% mortality rate and the abortion rate in pregnant cows was 30–40% [ 31 ].…”
Section: Epidemiology Of Rvfmentioning
confidence: 99%